2021
DOI: 10.1136/bmjopen-2021-051115
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with serious psychological distress during the COVID-19 pandemic in Japan: a nationwide cross-sectional internet-based study

Abstract: ObjectiveTo investigate the factors associated with serious psychological distress (SPD) during the COVID-19 pandemic in Japan.DesignNationwide cross-sectional study using survey data.SettingInternet survey using sampling weights for national estimates conducted between 25 August and 30 September 2020 in Japan.ExposuresDemographics (age, gender), socioeconomic status (income level, employment type, educational attainment, marital status, family composition and caregiving burden); the experience of domestic vio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 48 publications
2
45
0
1
Order By: Relevance
“…Although several variables have demonstrated a negative impact on mental health in the general population, little is known about which factors had a greater impact in predicting women’s psychological distress during the pandemic. Previous studies [ 24 , 25 , 26 ] have examined gender differences in psychological distress after the COVID-19 pandemic, and reported several important factors that were associated with a higher level of mental health problems. In a study conducted in China, Yan et al [ 25 ] found that among female participants, risk factors of distress included poorer health, worse local pandemic status, greater desire for knowledge about COVID-19, the problem of diseases during the pandemic, and an inability to work/study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several variables have demonstrated a negative impact on mental health in the general population, little is known about which factors had a greater impact in predicting women’s psychological distress during the pandemic. Previous studies [ 24 , 25 , 26 ] have examined gender differences in psychological distress after the COVID-19 pandemic, and reported several important factors that were associated with a higher level of mental health problems. In a study conducted in China, Yan et al [ 25 ] found that among female participants, risk factors of distress included poorer health, worse local pandemic status, greater desire for knowledge about COVID-19, the problem of diseases during the pandemic, and an inability to work/study.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, calmness of mood compared with the pre-pandemic period and frequent contact with colleagues were found to act as protective factors against psychological distress. Another recent study [ 26 ] found that the caregiving burden, domestic violence, and fear of COVID-19 were independently associated with psychological distress among young women, who presented higher suicide rates during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Another large-scale survey of psychological distress among the general population in Japan was conducted between August and September 2020. 17 In this survey, gender (women), age (younger), income level, employment type, caregiving status, domestic violence experience, and fear of COVID-19 were independently associated with serious psychological distress (SPD). However, this study had not targeted pregnant women, who may have additional risk factors for SPD such as a history of miscarriage and abortion.…”
Section: Introductionmentioning
confidence: 86%
“…Economic stress can affect mental health 21 and low income is also associated with poorer mental health. 12,22 Since the leave of absence and shortening of business hours directly affects the worker's economic situation, it may have led to increased psychological distress. The second survey of this study was conducted on the days, February 18-19th, 2021; prior to that, a state of emergency was re-declared from January 8th.…”
Section: Discussionmentioning
confidence: 99%